ChatGPT, Metaverses and the Future of Transdisciplinary Communication - Jasmin (Bey) Cowin (Journal of Systemics, Cybernetics and Informatics)

(untitled)
The emergence of artificial intelligence (AI) and virtual reality (VR) technologies has propelled human-machine interaction and immersive experiences to unprecedented levels. Current discussions revolve around Trans-disciplinarity, transdisciplinary communication, metaverses2, and a paradigm shift ushered in by ChatGPT, an intelligent conversational agent powered by OpenAI's GPT-3.5 architecture. Its integration into VR and metaverses for education and transdisciplinary communication is also being explored. The objective is to discuss and reframe ethical issues arising within the global discourse surrounding technology adaptation, and the innate promises, potential, and pitfalls. By examining the technical and ethical implications of such a potential integration, the paper aims to uncover the broader contexts of these advancements. A deeper understanding of the challenges ahead can be achieved by critically examining the risks and opportunities presented by ChatGPT, virtual realities, and metaverses. The paper emphasizes the need for initiative-taking measures to guide the development and deployment of these transformative technologies. Furthermore, the intersection of AI, VR, metaverses, education, transdisciplinarity, and transdisciplinary communication will be investigated and examined.